2022
DOI: 10.1002/jcph.2147
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Histamine H2 Receptor Antagonists: An Umbrella Review of Meta‐Analyses

Abstract: Histamine H2 receptor antagonists (H2RAs) were widely used to inhibit gastric acid secretion, but its association with adverse events remains controversial and unclear. We conducted an umbrella review of meta-analyses to systematically assess the quality and credibility of the correlations between H2RA use with the risk of adverse outcomes through searching 4 major databases from inception to April 30, 2022. Forty-six individual metaanalyses were identified, including 29 meta-analyses of observation studies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In this regard, H2RAs may have certain advantages over β-blockers. An important point is that most H2RAs are over-the-counter drugs in most countries with relatively low market price and moderately safe profile according to our previous evidence-based analysis ( Meng et al, 2023 ), which provided a much safer potential treatment strategy for HF as compared with β-blockers especially considering that most chronic HF patients need long-term or even lifelong medication. Furthermore, although it is well acknowledged that β-blockers have good curative effect for patients with HFrEF, little evidence supports the benefits of β-blockers in HF with preserved ejection fraction (HFpEF) ( Cleland et al, 2018 ; Meyer and Lewinter, 2019 ; Brinker et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, H2RAs may have certain advantages over β-blockers. An important point is that most H2RAs are over-the-counter drugs in most countries with relatively low market price and moderately safe profile according to our previous evidence-based analysis ( Meng et al, 2023 ), which provided a much safer potential treatment strategy for HF as compared with β-blockers especially considering that most chronic HF patients need long-term or even lifelong medication. Furthermore, although it is well acknowledged that β-blockers have good curative effect for patients with HFrEF, little evidence supports the benefits of β-blockers in HF with preserved ejection fraction (HFpEF) ( Cleland et al, 2018 ; Meyer and Lewinter, 2019 ; Brinker et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For several decades, it has long been suggested that histamine H2 receptor (H2R) was highly related to occurrence and development of HF and, as a result, might be a novel promising anti-HF target ( Hara et al, 2002 ; Leary et al, 2014 ; Leary et al, 2016 ; Saheera et al, 2022 ). In this regard, the anti-HF effects of histamine H2 receptor antagonists (H2RAs) consequently gained particular attention in the following related clinical investigations, based on which it was suggested that H2RAs had beneficial effects on short- and medium-term outcomes of HF patients ( Adelborg et al, 2018 ; Zhang et al, 2018 ; Huang et al, 2022 ) and exhibited relatively safe profile in cardiovascular system ( Meng et al, 2023 ). Nevertheless, these findings also raised another key question that whether the use of H2RAs has considerable treatment value as compared with other traditional anti-HF drugs, elucidating of which will eventually provide further evidence to promote the clinical application of H2RAs in treatment of HF.…”
Section: Introductionmentioning
confidence: 99%